ANALYSIS OF THE PERFORMANCE OF POKDARWIS IN NGADISARI VILLAGE TO SUPPORT SUSTAINABLE TOURISM PROGRAMS - Juniarsa, Nurtjahja; Ajisaputra, Arnanda; Anggoro, Yudhi (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
Ngadisari Village features distinctive natural and cultural attractions that hold significant potential to draw both local and international tourists. Nonetheless, this potential is impeded by various internal and external factors. This study seeks to identify the factors influencing the performance of Pokdarwis in Ngadisari Village, the community institution tasked with maintaining tourism attractions and sustainability. The research uses an associative quantitative method with 100 respondents. Data were analyzed using SEM-PLS, resulting in the rejection of Hypotheses 3 and 4, while the remaining hypotheses were supported. The performance of Pokdarwis in Ngadisari Village is influenced 85.4% by exogenous variables, whereas Religiosity is influenced 58.9% by endogenous variables. The findings suggest that Pokdarwis’ performance in Ngadisari Village is centered on achieving goals with a strong Dharma culture but lacks adequate attention to the socio-economic aspects of sustainable tourism programs.